A study Assessing the Challages Faced by Disabled Elderly People in Rural Areas of Busia District With Spacific Reference to Busitema Sub County - Wandera Charles . (Kampala : Uganda Christian University Mukono, 2011)
Description Catalouging Uganda Christian University Mukono Dissertation BSWASA
Includes References (p.31-33)
Keywords: Challages of Disabled